Exploring the potential of saponins as adjuvants in lipid-nanoparticle-based mRNA vaccines - Yulia Eygeris; Antony Jozic; Michael I. Henderson; Dylan Nelson; Gaurav Sahay (Molecular Therapy: Methods & Clinical Development)
Saponins are a class of phytocompounds known for their amphiphilic properties. Here, we have evaluated incorporation of 40 saponins into a model lipid nanoparticle (LNP) formulation and evaluated their performance in vitro and in vivo. We reasoned that the surfactant activity of saponins could be beneficial in the context of cell and gene therapy due to the disruption of the intracellular membranes. We established formulation methodology to incorporate saponins into LNPs and measured their endosomal disruption and transfection efficiency with DNA barcode and mRNA cargoes. We identified two saponins—quillaic acid and macranthoidin B—that increase the LNP transfection efficiency and endosomal disruption. Saponin formulations demonstrated cargo-dependent activation of the innate immune system, as measured by the cell-based assays of interferon regulatory factor (IRF) and NF-κB pathway activation. Quillaic acid LNPs resulted in higher titers of anti-OVA IgG2a in the vaccination studies compared to a “naive” LNP control, which suggests a more Th1-biased immunopathology of these vaccines. As Th2-biased vaccines can trigger an allergic response, an mRNA vaccine with a balanced Th1/Th2 response is more favorable for translation into the clinic. Overall, quillaic acid may serve as an adjuvant for mRNA vaccines and potentially decrease the risk of vaccine-associated adverse events.